Evaluation of the Perceptions, Attitudes and Practices among Greek Non-Professional Athletes Visiting a Public Hospital during March 2022, towards COVID-19 Vaccination and Its Consequences on Sports Training and Sports Activity - Georgios Marinos; Dimitrios Lamprinos; Panagiotis Georgakopoulos; Nikiforos Kavoukidis; Evangelos Oikonomou; Georgios Zoumpoulis; Gerasimos Siasos; Dimitrios Schizas; Alexandros Nikolopoulos; Petros G. Botonis; Christos Damaskos; Georgios Rachiotis; et al. (Vaccines, 2022)
Sports have been majorly impacted by the COVID-19 pandemic. After the lockdown period, vaccination and protocols were implemented to return to normality. We aimed to assess the attitudes and practices related to COVID-19 vaccination among athletes, and to record adverse effects of vaccination, if any. A questionnaire was distributed to 1012 male and female athletes, 15+ years old, within the region of Athens. Vaccination coverage with at least one dose was 93.5%, whereas 53.9% were fully vaccinated. More than half of the participants were infected with SARS-CoV-2 at the time of the study. More than 90% of the participants, considered the vaccines as safe, effective and important for public health. Concern about potential side-effects was raised especially by women athletes (59.1% of women compared to 42.2% of men, p < 0.001). The main reasons for avoiding vaccination were fear of vaccine safety, concern about the short time period for vaccine development and testing and doubt of risk of being exposed to SARS-CoV-2 infection. The main reported side-effects were pain at the injection site, fatigue, fever and headache. Approximately two thirds of the participants reported that vaccination did not affect their training, and none reported missing participation in scheduled athletic events. Participants reported high compliance to preventive measures by themselves and fellow athletes, but low satisfaction regarding the implementation of public protocols and the flow of information provided by the authorities. Athletes of older age and those less concerned about potential side-effects were more likely to get fully vaccinated. Nevertheless, the vast majority of the athletes in our study were vaccinated for COVID-19 despite any hesitation regarding effectiveness, safety, or potential side-effects from the vaccines.